2012
DOI: 10.1192/pb.bp.111.037903
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' health: stigma and the professional discomfort in seeking help

Abstract: SummaryI describe the needs for and impediments in provision of psychological support services for doctors. Morbidity and the resistance in the profession to addressing their own health needs are discussed. I also explore the principles of bespoke services for doctors, with particular emphasis on overcoming stigma and facilitating therapeutic engagement. I argue that triage is an inappropriate service model of care for doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 14 publications
2
35
0
1
Order By: Relevance
“…Within the civilian sector, attempts to overcome this challenge have included the provision of separate and confidential services for medical personnel. Garelick27 suggests that self-referral to a confidential psychological service with easy access to a face-to-face consultation may make it easier to overcome barriers to care. Additionally, other care pathway entry points such as online or remotely delivered therapies, which have been shown to be effective for some mental health problems such as depression and obsessive compulsive disorder, might further promote access to care 28–30.…”
Section: Discussionmentioning
confidence: 99%
“…Within the civilian sector, attempts to overcome this challenge have included the provision of separate and confidential services for medical personnel. Garelick27 suggests that self-referral to a confidential psychological service with easy access to a face-to-face consultation may make it easier to overcome barriers to care. Additionally, other care pathway entry points such as online or remotely delivered therapies, which have been shown to be effective for some mental health problems such as depression and obsessive compulsive disorder, might further promote access to care 28–30.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also confirm the continued perceived stigma around mental illness. 14,15,30 The findings suggest this may be a particular problem for those working in general practice.…”
Section: Comparison With Existing Literaturementioning
confidence: 90%
“…Continued attendance at work while unwell has been reported previously, 7,14,27,28 and it has been suggested that this lack of self-care may result in longer periods of time off sick further down the line. 29 These findings add depth to this information around 'presenteeism', by showing the degree of guilt associated with the pressure to stay at work that can drive this unhealthy practice.…”
Section: Comparison With Existing Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…An editorial in The Psychiatrist describing the obstacles experienced by medical professionals seeking and receiving help for mental illness has highlighted this case again [2]. …”
Section: Commentarymentioning
confidence: 99%